First E- and D- region incoherent scatter spectra observed over Jicamarca - Chau Chong Shing, Jorge Luis (2006)
We present here the first Jicamarca observations of incoherent scatter radar (ISR) spectra detected from E- and D-region altitudes. In the past such observations have not been possible at Jicamarca due a combined effect of strong equatorial electrojet (EEJ) clutter and hardware limitations in the receiving system. The observations presented here were made during weak EEJ conditions (i.e., almost zero zonal electric field) using an improved digital receiving system with a wide dynamic range and a high data throughput. The observed ISR spectra from E- and D-region altitudes are, as expected, narrow and get even narrower with decreasing altitude due to increasing ion-neutral collision frequencies. Therefore, it was possible to obtain accurate spectral measurements using a pulse-to-pulse data analysis. At lower altitudes in the D-region where signal correlation times are relatively long we used coherent integration to improve the signal-to-noise ratio of the collected data samples. The spectral estimates were fitted using a standard incoherent scatter (IS) spectral model between 87 and 120 km, and a Lorentzian function below 110 km. Our preliminary estimates of temperature and ion-neutral collisions frequencies above 87 km are in good agreement with the MSISE-90 model. Below 87 km, the measured spectral widths are larger than expected, causing an overestimation of the temperatures, most likely due to spectral distortions caused by atmospheric turbulence.